The Role of Job Satisfaction as a Mediator: Exploring the Impact of Communication Quality and Principal Conflict Management on Teacher Performance - Prasetyo, Hadi; Malik, Nazaruddin; Mohyi, Achmad (Business Innovation Management and Entrepreneurship Journal, 2023)
The purpose of the study was to analyze and test the effect of communication quality and principal conflict management on the performance of elementary / MI teachers in Trenggalek Regency with job satisfaction as an intervening variable. Explanatory research is a type of research used in research with a quantitative approach and data collection methods using survey methods Types of research using explanatory research types, survey methods by giving questionnaires to 132 teachers as respondents. The SEM-PLS method is used in data analysis and testing with the help of the SmartPLS 3 application program. The results of the direct test found that the quality of principal communication, principal conflict management, and job satisfaction each had a positive and significant influence on teacher performance, the quality of principal communication and principal conflict management each had a positive and significant effect on teacher job satisfaction. The results of indirect influence testing with the results that teacher job satisfaction was able to mediate the influence between the quality of principal communication and the principal's conflict management on teacher performance positively and significantly.